The Nitric Oxide Donor SNAP-Induced Amino Acid Neurotransmitter Release in Cortical Neurons. Effects of Blockers of Voltage-Dependent Sodium and Calcium Channels - Merino, José Joaquín; Arce, Carmen; Naddaf, Ahmad; Bellver-Landete, Victor; Oset-Gasque, Maria Jesús; González, María Pilar (PLOS ONE, 2014)
Background The discovery that nitric oxide (NO) functions as a signalling molecule in the nervous system has radically changed the concept of neuronal communication. NO induces the release of amino acid neurotransmitters but the underlying mechanisms remain to be elucidated. Findings The aim of this work was to study the effect of NO on amino acid neurotransmitter release (Asp, Glu, Gly and GABA) in cortical neurons as well as the mechanism underlying the release of these neurotransmitters. Cortical neurons were stimulated with SNAP, a NO donor, and the release of different amino acid neurotransmitters was measured by HPLC. The involvement of voltage dependent Na+ and Ca2+ channels as well as cGMP in its mechanism of action was evaluated. Conclusions Our results indicate that NO induces release of aspartate, glutamate, glycine and GABA in cortical neurons and that this release is inhibited by ODQ, an inhibitor of soluble guanylate cyclase. Thus, the NO effect on amino acid neurotransmission could be mediated by cGMP formation in cortical neurons. Our data also demonstrate that the Na+ and Ca2+ voltage- dependent calcium channels are involved in the NO effects on cortical neurons.